Shale Microstructure Characteristics under the Action of Supercritical Carbon Dioxide (Sc-CO2) - Chunsheng Yu; Xiao Zhao; Qi Jiang; Xiaosha Lin; Hengyuan Gong; Xuanqing Chen (Energies, 2022)
Supercritical carbon dioxide (SC-CO2) is suitable to extract low-polar organics and to assist in the dissolution of pores and fractures in shale. In this work, we investigate the effect of temperature on the structure of five shale samples via high pressure reaction assisted with SC-CO2. Shale samples were analyzed using X-ray diffraction, field emission scanning electron microscopy, and ImageJ software. Due to the extraction of CO2, after Sc-CO2 treatment, carbonate and clay content decreased, while quartz and plagioclase increased slightly, which improved gas and oil flow in microscopic pores and shale cracks. Shale samples showed an increase in surface fracture area as experimental temperature increased. Since Sc-CO2 fluid density and solubility increase with temperature, more organics can be extracted from shale pores and fractures, resulting in newly formed pores and fractures. As a result, the threshold temperature for shale high-temperature Sc-CO2 cracking was confirmed to be 400 °C, and the fracture area increased by more than 45% at this temperature. Based on the findings of this study, Sc-CO2 technology can be used to potentially recover low-maturity shale oil efficiently.